2019
DOI: 10.3390/medicines6030072
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pruritus Responding to Dupilumab—A Case Series

Abstract: Background: Chronic pruritus is defined as itch lasting for greater than six weeks. Pruritus is a burdensome manifestation of several internal and external disease states with a significant impact on quality of life. Dupilumab has shown promise in treating a number of conditions including atopic dermatitis (AD) and asthma. Its success in reducing pruritus in AD has generated interest regarding its potential application in other pruritic conditions, such as chronic pruritus of unknown origin, uremic pruritus, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
52
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 80 publications
4
52
0
2
Order By: Relevance
“…In the literature, some cases of PN were reported that were successfully treated with dupilumab, showing efficacy in reducing the itch (Beck, Yang, Sekhon, Bhutani, & Liao, ; Calugareanu et al, ; Ferrucci, Tavecchio, Berti, & Angileri, ; Mollanazar, Elgash, Weaver, et al, ; Napolitano et al, ; PH1 & JO2, ; Tanis, Ferenczi, & Payette, ; Zhai et al, ).…”
mentioning
confidence: 99%
“…In the literature, some cases of PN were reported that were successfully treated with dupilumab, showing efficacy in reducing the itch (Beck, Yang, Sekhon, Bhutani, & Liao, ; Calugareanu et al, ; Ferrucci, Tavecchio, Berti, & Angileri, ; Mollanazar, Elgash, Weaver, et al, ; Napolitano et al, ; PH1 & JO2, ; Tanis, Ferenczi, & Payette, ; Zhai et al, ).…”
mentioning
confidence: 99%
“…Eine rezente Untersuchung zeigte eine gesteigerte [9]. Im Gegensatz zu unserer Patientin war das subjektive Ansprechen (Reduktion des Pruritus) in den meisten Fällen deutlich früher zu beobachten [10][11][12][13][14]. Nur wenige dieser Patienten zeigten ein langsameres Ansprechen auf die Behandlung mit Dupilumab.…”
Section: Clinical Letterunclassified
“…3,4 The world literature on eosinophilic dermatosis of hematologic malignancy (EDHM) was recently reviewed 5 ; to the best of my knowledge, 206 patients with this condition have been described (Table I). [3][4][5][6][7] EDHM has been observed more frequently in men (55% [107 of 193 patients]) than in women (45% [86 of 193 patients]); sex was not provided for 13 patients.…”
mentioning
confidence: 99%